2017
DOI: 10.1653/024.100.0127
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Appearance and Population Outbreak ofEunica monima(Lepidoptera: Nymphalidae) on Desecheo Island, Puerto Rico

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…On Desecheo Island, several positive outcomes have been documented after the invasive mammal eradications, including an increase in the native cactus Harrisia portoricensis , arthropods such as butterflies, grasshoppers, and crabs (Shiels et al 2017), and seabird nesting, particularly Bridled Terns (Island Conservation, unpubl. report).…”
Section: Discussionmentioning
confidence: 99%

Desecheo Island: a new home for Audubon's Shearwaters (<em>Puffinus lherminieri</em>)

Luis A. Ramos-Vázquez,
Nahíra Arocho-Hernández,
Cielo Figuerola-Hernández
et al. 2024
JCO
“…On Desecheo Island, several positive outcomes have been documented after the invasive mammal eradications, including an increase in the native cactus Harrisia portoricensis , arthropods such as butterflies, grasshoppers, and crabs (Shiels et al 2017), and seabird nesting, particularly Bridled Terns (Island Conservation, unpubl. report).…”
Section: Discussionmentioning
confidence: 99%

Desecheo Island: a new home for Audubon's Shearwaters (<em>Puffinus lherminieri</em>)

Luis A. Ramos-Vázquez,
Nahíra Arocho-Hernández,
Cielo Figuerola-Hernández
et al. 2024
JCO
“…Following cessation of bombing and subsequent designation as a NWR in 1976, managers eradicated damaging invasive and non‐native rats, goats and macaques from Desecheo to support biodiversity conservation goals and enable other restoration techniques, as seen elsewhere around the world (Jones et al., 2016). On Desecheo Island, several positive outcomes were documented following invasive mammal eradication, including an increase in the native cactus Harrisia portoricensis (Figuero, 2017) and arthropods such as butterflies, grasshoppers and crabs (Shiels et al., 2017). However, seabird response was limited, with no observed changes in the number of bridled tern or brown noddy breeding pairs across the island (Island Conservation, 2013; McKown, 2009; Wolf et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary differentiation between bats that consume soft‐bodied lepidopterans and those that consume hard‐bodied insects was found to be a mechanism for the coexistence of multiple mormoopid bat species (Rolfe & Kurta, 2012). Another study found that the removal of an invasive rat ( Rattus rattus ) from Desecheo Island was immediately followed by an outbreak of the uncommon dingy purplewing butterfly (Nymphalidae: Eunica monima ), with population release from rat predation as one possible explanation (Shiels et al., 2017). The relationship between anole lizards and lepidopteran agricultural pests has also been investigated, as predation by lizards is a viable form of biological control for some Lepidoptera species (Borkhataria et al., 2006; Perfecto et al., 2021; Segarra‐Carmona & Barbosa, 1988).…”
Section: Ecologymentioning
confidence: 99%